Etiology, risk factors and complications of exercise induced muscle injury - Sunbol, Khalid M.; Althiyabi, Fahad S.; Alshuria, Abdulaziz A.; Alajwad, Mahdi H.; Mahlawi, Amoudi M.; Alsayed, Budur H.; Alsarhan, Mustafa O.; Alshehri, Rahaf A.; Alsahli, Abdulaziz A.; Alhazmi, Khalid A.; Esmael, Emtenan A. (International Journal Of Community Medicine And Public Health, 2022)
Healthy lifestyle includes physical activity as the basic component however, exercises with eccentricity have been associated to a higher risk of muscle injury and slower recovery. The development of exercise-induced muscle injury is a phenomenon that results from atypical or unaccustomed activity; the intensity of the pain and the extent of the damage steadily deteriorate over time, and when the exercise session contains an eccentric component, they may last for several days. Increasing levels of muscle-specific circulating protein are present, along with increased levels of muscular pain and decreased muscle strength. The extent of severity of the symptoms following eccentric exercise varies greatly. Exercise-induced muscle injury is influenced by a number of factors including intensity, duration, mode, muscle group, age, gender, genetics, and dietary state. Numerous scientific studies illustrate the circumstances under which exercise causes muscle injury. It is widely acknowledged that exercise that is unfamiliar, particularly exercise that involves eccentric contractions, causes damage. exercise-induced muscle injury is accompanied by an inflammatory response involving numerous mediators, including the production of muscle-specific creatine kinase and interleukins and interleukins receptor antagonist and acute phase proteins. Complications of exercise-induced muscle injury include temporary muscle inflammation, loss of strength, muscle discomfort, restricted range of motion, elevated passive tension, discomfort, and a momentary decline in insulin sensitivity and can also lead to rhabdomyolysis. The purpose of this research is to review the available information about an etiology, risk factors and complications of exercise-induced muscle injury.